Legal Politics of Corruption Crimes from the Perspective of Islamic Criminal Law as a Restoration of Community Welfare Rights - Setia Miko; Sastri Aida Zuhra (PT. Education Research Center, 2025)
This article discusses the legal politics of eradicating corruption crimes from the perspective of fiqh jinayat (Islamic criminal jurisprudence) as a means of restoring community welfare rights. Corruption in Indonesia has become a structural phenomenon that not only damages state finances but also undermines social and economic justice. This study employs a library research method with a descriptive-analytical approach, analyzing various sources of positive criminal law and Islamic legal texts. The findings indicate that conventional punitive approaches have proven insufficient in combating corruption, as they often fail to address the root issue of public welfare losses. In Islamic law, corruption is classified as ghulul (embezzlement), risywah (bribery), and betrayal of public trust, and in certain cases may even be categorized as hirabah (grave criminal acts). Sanctions under fiqh jinayat include ta’zir, hudud, and in extreme cases, hirabah punishments, as well as asset confiscation as a tangible effort to recover public losses. The implementation of restorative justice is offered as a strategic alternative to shift from merely retributive justice to a more balanced model that incorporates social justice. Progressive legislation such as the ratification of the Asset Forfeiture Bill is essential to strengthen the state’s commitment in returning rights usurped by corrupt practices. This study recommends harmonizing national law with Islamic legal principles to build a more just, firm, and welfare-oriented legal system